Laying off employees expert solutions to everyday challenges. - Harvard Business School. Press (Boston, Mass. : Harvard Business Press, 2009)
Implementing a layoff is one of the most difficult and painful challenges a manager can face. Handled skillfully and compassionately, a layoff can set your team and your company on a positive new path; but, when handled improperly, layoffs can have negative effects that impact morale, productivity and more.
Includes bibliographical references.
Description based on print version record.
Keywords: Downsizing of organizations; Layoff systems; Employees -- Dismissal of; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books